PILOT STUDY ON PHARMACEUTICAL PROCESS OF MAMSA ARKA - A FORGOTTEN AMBROSIA - Ram, *G. Siva; Maheshwar, T.; Babu, G. (International Journal of Ayurveda and Pharma Research, 2016)
Arka kalpana (distillation) is a unique preparation of Bhaishajya kalpana. Mamsa Arka (meat distillate) among Arka kalpana is not much popular these days. It is practically forgotten and not practiced in modern Ayurveda. In classical literature Mamsa Arka is compared to ambrosia and best of all Arka formulations. Its properties are Maha Swadu (relishing) and Adhika rochana (enhances taste). It is also specifically given to certain patients having aversion to meat. Present study focuses on the pharmaceutical preparation of Mamsa Arka with special reference to Arka prakasa and performing organoleptic tests on the sample obtained. Experiment was done on a household stove to specify that Mamsa Arka can be prepared in small scale by the practitioner himself with ease. Simple distillation apparatus was used for the procedure. Temperature was maintained around 1200 to 1300 Celsius throughout the process with the help of thermometer which lasted for 1 ½ hour. The resultant distillate obtained was 1/3rd (33.3 % approx.) of the total liquid content in the mixture. Mamsa Arka is a colourless liquid with a specific odour dominated by Lavanga and Karpura. It is a palatable product with Madhura (Sweet), Tikta (Bitter) and slightly Katu (Pungent) Rasa (taste). Mamsa Arka is considered Laghu (light in digestion), Balya (strength promoting) and fast acting.